2002
DOI: 10.1053/ejvs.2001.1564
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Gender Difference on the Outcomes of Infrainguinal Bypass for Critical Limb Ischaemia in Chinese Patients

Abstract: following infrainguinal bypass for critical limb ischaemia, early results were similar in both gender groups. In the long-term, women patients suffered from significantly higher graft failure rate. However, their long-term survival and limb salvage rate remained comparable to those of men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 21 publications
5
62
0
Order By: Relevance
“…Despite the observation that native arterial diameters for woman are smaller than for men of the same age, 63 the published evidence base does not demonstrate a differential accuracy of stenosis assessment by gender. 64 No published studies have been designed or completed specifically to evaluate gender-based diagnostic accuracy.…”
Section: Pad Diagnostic Methods In Womenmentioning
confidence: 95%
See 3 more Smart Citations
“…Despite the observation that native arterial diameters for woman are smaller than for men of the same age, 63 the published evidence base does not demonstrate a differential accuracy of stenosis assessment by gender. 64 No published studies have been designed or completed specifically to evaluate gender-based diagnostic accuracy.…”
Section: Pad Diagnostic Methods In Womenmentioning
confidence: 95%
“…Egorova et al 277 found a lower rate of procedural revascularization in women during inpatient hospitalization for PAD (46% versus 54%), although others have reported similar rates of revascularization between genders. 40 Several studies have observed that women undergoing lower extremity revascularization for PAD are older, 63,192,224,246,262 have more advanced disease, 234,262,277 and have a lower prevalence of smoking 63,246,262 than men. Hultgren et al 246 reported a higher proportion of suprainguinal procedures among women undergoing revascularization for PAD (44% versus 19%); conversely, others have reported lower rates of bypass to tibialevel outflow vessels in women.…”
Section: Gender and Patient Selection For Lower Extremity Revascularimentioning
confidence: 99%
See 2 more Smart Citations
“…21 In terms of anatomic factors, women have been noted to have smaller native and conduit vessel sizes, both of which have been correlated with poor surgical outcomes. 22,23 Furthermore, a higher occurrence of periprocedural bleeding and infectious complications leading to higher morbidity and mortality has been demonstrated among female patients. 19,22 Although men achieved a greater absolute mortality reduction compared with women between study decades (2.25% for men versus 1.65% for women), this difference does not appear to be clinically meaningful.…”
Section: Discussionmentioning
confidence: 99%